2012
DOI: 10.2527/jas.2011-4799
|View full text |Cite
|
Sign up to set email alerts
|

Early postmortem gene expression and its relationship to composition and quality traits in pig Longissimus dorsi muscle1

Abstract: An mRNA expression study has been performed in 20- to 25-min postmortem-obtained samples from Longissimus dorsi muscle of 59 Duroc × Landrace/ Large White (LD/LW) pigs to search for gene sequences related to meat quality (pH(24), pH(45), "Lab" color coordinates, curing yield, and exudation at 3 different times) or meat composition [intramuscular fat, content of several fatty acids (C16:0, C18:0, C18:1, and C18:2), ratio of saturated, monounsaturated, and polyunsaturated fatty acids, and protein and humidity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Cui et al [54] also proposed that these pathways play an important role in the intramuscular fat deposition in chicken. Cánovas et al [59] identified the ECM-receptor interaction and TGF-beta signaling pathways as the most relevant metabolic pathways represented in the list of DEG related with meat composition in pig longissimus dorsi muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al [54] also proposed that these pathways play an important role in the intramuscular fat deposition in chicken. Cánovas et al [59] identified the ECM-receptor interaction and TGF-beta signaling pathways as the most relevant metabolic pathways represented in the list of DEG related with meat composition in pig longissimus dorsi muscle.…”
Section: Discussionmentioning
confidence: 99%
“…However we cannot presume if this results from dissimilar muscle maturity and/or from regeneration process occurring mainly in SM. This variability could affect muscle development and hence meat quality traits [13], [69], thus skeletal muscle specificity should be taken into account to determine important features for meat quality traits and identify useful biomarkers of pork quality.…”
Section: Discussionmentioning
confidence: 99%